Pre-qualiﬁcation documents for waterprooﬁng subcontractor - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the pre-qualiﬁcation documents for waterprooﬁng subcontractor of Brac University new campus development project .